1985
DOI: 10.1128/iai.50.2.392-397.1985
|View full text |Cite
|
Sign up to set email alerts
|

The ability of Salmonella typhimurium to produce the siderophore enterobactin is not a virulence factor in mouse typhoid

Abstract: One of the nonspecific defense mechanisms of higher animals is their ability to limit iron availability to infecting bacteria. Thus it has been argued that all pathogenic bacteria must have special mechanisms to obtain iron in the host environment. Salmonella typhimurium is known to produce a siderophore, enterobactin, with which it can obtain iron from host transferrin. Previous studies have indicated that the production of this molecule is necessary for the ability of intraperitoneally injected. S. typhimuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
2

Year Published

1986
1986
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 41 publications
(55 reference statements)
8
36
2
Order By: Relevance
“…Since serovar Typhi strains attenuated for human beings are known to grow poorly in human macrophages [16], restricted growth of these tonB and ent 3 mutants in human monocytic cells is consistent with a decrease in virulence. The di¡erence between our ¢ndings in serovar Typhi and those of others in serovar Typhimurium [12,21] suggests that iron uptake requirements di¡er between these two S. enterica serovars. This speculation is consistent with the observation that serovar Typhi strains express lower levels of enterochelin than do serovar Typhimurium strains [22], and that mucin containing iron is needed for serovar Typhi to infect mice [23].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Since serovar Typhi strains attenuated for human beings are known to grow poorly in human macrophages [16], restricted growth of these tonB and ent 3 mutants in human monocytic cells is consistent with a decrease in virulence. The di¡erence between our ¢ndings in serovar Typhi and those of others in serovar Typhimurium [12,21] suggests that iron uptake requirements di¡er between these two S. enterica serovars. This speculation is consistent with the observation that serovar Typhi strains express lower levels of enterochelin than do serovar Typhimurium strains [22], and that mucin containing iron is needed for serovar Typhi to infect mice [23].…”
Section: Discussioncontrasting
confidence: 77%
“…PII: S 0 3 7 8 -1 0 9 7 ( 0 1 ) 0 0 0 2 6 -X presence of unsaturated transferrin or human sera, and were signi¢cantly less virulent than wild-type strains in a mouse model of disease [3]. These results in serovar Typhi were in clear contrast to results in serovar Typhimurium, where ent 3 strains are commonly as virulent for mice as wild-type strains [3,12]. Because we have shown that the enterochelin system is expressed in vivo in patients with typhoid fever [13], we believe that serovar Typhi iron uptake-de¢cient mutants are likely to be attenuated for human cells.…”
Section: Introductionmentioning
confidence: 96%
“…While this is relatively low, and as such may constitute a signal for induction of virulence genes, it is probably sufficient to meet the iron requirements of the internalised bacteria. This would be consistent with findings that S. typhimurium virulence is not dependent on high-affinity iron uptake systems utilising siderophores [70,72]. Little is known about the ways that successful intraceilular pathogens circumvent the iron depletion responses discussed above.…”
Section: Occupation Of An Intracellular Nichesupporting
confidence: 86%
“…Some parasitic microorganisms, such as Listeria [64], Yersinia [69], Salmonella [70] and Shigella [53] species, occupy intracellular niches. After internalisation, Shigella species and Listeria monocytogenes escape from the vacuole into the cytoplasm where they may obtain iron from ferritin or haem [22,53].…”
Section: Occupation Of An Intracellular Nichementioning
confidence: 99%
See 1 more Smart Citation